Calcium intake, levels and supplementation and effect modification by genetic variation of calcium homeostasis on the risk of colorectal cancer: the Rotterdam study. Issue 5 (23rd December 2020) - Araghi, Sadaf Oliai; Jayakkumaran, Abi; Mulder, Marlies; Stricker, Bruno H.; Ruiter, Rikje; Kiefte-de Jong, Jessica C.
Abstract : Supplemental Digital Content is available in the text. Abstract : Objectives: Previous studies showed that high calcium intake may be associated with the reduced colorectal cancer (CRC) risk, but results were inconclusive. In this study, we evaluated whether calcium intake from diet and supplements, as well as the calcium levels itself, were associated with the CRC risk in middle-aged and older individuals. Also, we evaluated whether these associations were modified by genetic variation of calcium homeostasis. Design: This study was embedded in the Rotterdam study, a prospective cohort study among adults aged 55 years and older without CRC at baseline, from the Ommoord district of Rotterdam, The Netherlands ( N  = 10 941). Effect modification by a predefined polygenetic risk score (PRS) from seven loci known to be associated with calcium concentrations, was evaluated. Results: The incidence rate of CRC in the study population was 2.9 per 1000 person-years. Relative to the recommended dietary calcium intake, only higher than the recommended dietary calcium intake (≥1485 mg/day) was associated with a reduced risk of CRC [hazard ratio (HR), 0.66; 95% confidence interval (CI), 0.44–1.00]. No significant associations were found for calcium supplementation and only in the subgroup analysis, albumin-adjusted calcium levels were associated with an increased risk of CRC (HR = 1.11; 95% CI, 1.00–1.23). PRS showed effect modification in the association between calcium intake and CRC ( P for interaction = 0.08). After stratification of PRS into low, intermediate and high, we found a lower CRC risk for low-weighted PRS per increase in calcium intake. Conclusion: There is no consistent association between calcium indices on CRC. However, the association between calcium intake and CRC may be modified by genetic variation associated with serum calcium concentrations that deserves further replication in other studies with different population.